Separator for lithium secondary battery, method for manufacturing the separator, and lithium secondary battery including the separator
By using a porous polymer substrate and a porous coating on the lithium secondary battery separator, the coating contains inorganic particles and thermosetting phenolic resin, the problem of insufficient heat shrinkage and heat resistance of the separator at high temperature is solved, and the problem of insufficient heat resistance of the separator is achieved High adhesion and heat resistance of the electrode are improved.
Patent Information
- Application Number
- CN202180013656.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-04-03
- Filing Date
- 2021-03-31
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2041-03-31
AI Technical Summary
The existing lithium secondary battery separators have problems of heat shrinkage and insufficient heat resistance in high temperature environments, resulting in a risk of short circuit between the cathode and the anode and poor adhesion to the electrode.
Porous polymer substrate plus a porous coating, the coating contains inorganic particles and a thermosetting phenolic resin with hydroxyl groups and aromatic rings, and the network structure is formed by thermal curing to improve heat resistance, and the thermosetting phenolic resin is used in the slurry. As a dispersant to enhance adhesion.
The heat resistance and thermal safety of the partition at high temperatures are improved, while maintaining high adhesion to the electrodes, reducing the amount of dispersant used, and enhancing the overall performance of the electrochemical device.
Smart Images

Figure BDA0003788835020000031 
Figure BDA0003788835020000032 
Figure BDA0003788835020000051
Abstract
Description
Technical Field
[0001] The present disclosure relates to a separator for a lithium secondary battery, a method of manufacturing the separator, and a lithium secondary battery including the separator.
[0002] This application claims the priority of Korean Patent Application No. 10-2020-0041002 filed in Korea on April 3, 2020, the disclosure of which is incorporated herein by reference. Background Art
[0003] Recently, energy storage technology has received increasing attention. As the application of energy storage technology has expanded to energy sources for mobile phones, cameras, and notebook PCs, and even to energy sources for electric vehicles, efforts to develop electrochemical devices have become increasingly a reality. In this context, electrochemical devices have attracted the most attention. Among these electrochemical devices, the development of rechargeable secondary batteries has been attracting much attention. Recently, in the process of developing these batteries, active research has been conducted on designing new electrodes and cells in order to improve capacity density and specific energy.
[0004] Among commercially available secondary batteries, lithium secondary batteries developed in the early 1990s have attracted much attention because they have higher operating voltage and significantly higher energy density than conventional batteries such as Ni-MH batteries, Ni-Cd batteries, and lead sulfate batteries using aqueous electrolytes.
[0005] Although these secondary batteries have been produced by many manufacturing companies, their safety characteristics show different signs. It is very important to evaluate and ensure the safety of these secondary batteries. The most important consideration is that the secondary batteries should not harm the user when they fail. For this purpose, safety standards strictly control fire and smoke in secondary batteries. For the safety characteristics of secondary batteries, special attention is paid to explosions when the secondary battery overheats to cause thermal runaway or perforation of the separator.
[0006] The separator prevents short circuits between the cathode and the anode and provides a lithium ion transmission channel. Therefore, the separator is an important factor affecting the safety and output characteristics of the battery. However, the polyolefin-based porous polymer substrate conventionally used as a separator for electrochemical devices exhibits severe thermal shrinkage behavior at temperatures of 130°C or higher due to its material properties and characteristics including orientation during its manufacturing process, thereby causing a short circuit between the cathode and the anode.
[0007] In this case, attempts have been made to apply a porous coating comprising inorganic particles and a thermoplastic binder polymer to a porous polymer substrate to increase heat resistance. When such a porous coating is formed, heat resistance can be improved compared to a porous polymer substrate used alone. However, when the separator is exposed to a high temperature environment higher than the melting point of the binder polymer, the improvement of thermal safety is limited.
[0008] At the same time, high adhesion is also required between the porous coating and the electrode. Summary of the invention
[0009] Technical issues
[0010] The present disclosure is intended to solve the problems of the prior art, and thus the present disclosure is intended to provide a separator for a lithium secondary battery, the separator having improved heat resistance and showing high adhesion to an electrode.
[0011] The present disclosure also aims to provide a method of manufacturing a separator for a lithium secondary battery having the above-mentioned characteristics.
[0012] Furthermore, the present disclosure aims to provide a lithium secondary battery including a separator having the above-mentioned characteristics.
[0013] Technical Solution
[0014] In one aspect of the present disclosure, a separator for a lithium secondary battery according to any one of the following embodiments is provided.
[0015] According to a first embodiment, there is provided a separator for a lithium secondary battery, comprising:
[0016] a porous polymer substrate having a plurality of pores; and
[0017] A porous coating layer is formed on at least one surface of the porous polymer substrate and includes a plurality of inorganic particles and a binder polymer, wherein the binder polymer includes a thermosetting phenolic resin having at least one hydroxyl group and an aromatic ring.
[0018] According to a second embodiment, there is provided a separator for a lithium secondary battery as defined in the first embodiment, wherein the thermosetting phenolic resin includes at least one of a novolac type phenolic resin represented by the following Chemical Formula 1 and a resole type phenolic resin represented by the following Chemical Formula 2:
[0019] [Chemical formula 1]
[0020]
[0021] In Chemical Formula 1, n is an integer of 1 or more, and R represents H and any one of an optionally substituted C1-C100 alkyl group, an alkoxy group, and an alkenyl group.
[0022] [Chemical formula 2]
[0023]
[0024] In Chemical Formula 2, n and m are each an integer of 1 or more, and R represents H and any one of an optionally substituted C1-C100 alkyl group, an alkoxy group, and an alkenyl group.
[0025] According to a third embodiment, there is provided a separator for a lithium secondary battery as defined in the first embodiment or the second embodiment,
[0026] The thermosetting phenolic resin is thermally cured at 120-200°C.
[0027] According to a fourth embodiment, there is provided a separator for a lithium secondary battery as defined in any one of the first to third embodiments,
[0028] The thermosetting phenolic resin is phenol-formaldehyde resin.
[0029] According to a fifth embodiment, there is provided a separator for a lithium secondary battery as defined in any one of the first to fourth embodiments,
[0030] Wherein, based on 100 wt % of the inorganic particles, the content of the thermosetting phenolic resin is 0.1-20 wt %.
[0031] According to a sixth embodiment, there is provided a separator for a lithium secondary battery as defined in any one of the first to fifth embodiments,
[0032] Wherein, based on 100 wt % of the content of the inorganic particles, the binder polymer further includes a non-phenolic resin in an amount of 0.1-50 wt %.
[0033] According to a seventh embodiment, there is provided a separator for a lithium secondary battery as defined in any one of the first to sixth embodiments,
[0034] The thickness of the porous polymer substrate is 1-20 μm.
[0035] And the thickness of the porous coating layer is 0.5-20 μm based on single-side coating.
[0036] In another aspect of the present disclosure, a method of manufacturing a separator according to any one of the following embodiments is provided.
[0037] According to an eighth embodiment, there is provided a method for manufacturing a separator for a lithium secondary battery, comprising the following steps:
[0038] (S1) preparing an inorganic particle dispersion by dispersing inorganic particles in a first solvent and dissolving a thermosetting phenolic resin having at least one hydroxyl group and an aromatic ring therein; and
[0039] (S2) coating a slurry for forming a porous coating layer including the inorganic particle dispersion on at least one surface of a porous polymer substrate, followed by drying to form a porous coating layer.
[0040] According to a ninth embodiment of the present disclosure, there is provided a method of manufacturing a separator for a lithium secondary battery as defined in the eighth embodiment,
[0041] The method further comprises the step of mixing the inorganic particle dispersion of step (S1) with a polymer solution comprising a non-phenolic resin dissolved in a second solvent.
[0042] According to the tenth embodiment of the present disclosure, a method for manufacturing a separator for a lithium secondary battery as defined in the ninth embodiment is provided, wherein the first solvent and the second solvent each independently include any one compound selected from water, C2-C5 alcohols, acetone, tetrahydrofuran, dichloromethane, chloroform, dimethylformamide, N-methyl-2-pyrrolidone, methyl ethyl ketone and cyclohexane, or a mixture of two or more thereof.
[0043] According to an eleventh embodiment of the present disclosure, there is provided a method of manufacturing a separator for a lithium secondary battery as defined in any one of the eighth to tenth embodiments, wherein the inorganic particle dispersion further includes a dispersant.
[0044] According to a twelfth embodiment of the present disclosure, there is provided a method for manufacturing a separator for a lithium secondary battery as defined in any one of the eighth to eleventh embodiments, wherein the thermosetting phenolic resin includes at least one of a novolac type phenolic resin represented by the following Chemical Formula 1 and a resole type phenolic resin represented by the following Chemical Formula 2:
[0045] [Chemical formula 1]
[0046]
[0047] In Chemical Formula 1, n is an integer of 1 or more, and R represents H and any one of an optionally substituted C1-C100 alkyl group, an alkoxy group, and an alkenyl group.
[0048] [Chemical formula 2]
[0049]
[0050] In Chemical Formula 2, n and m are each an integer of 1 or more, and R represents H and any one of an optionally substituted C1-C100 alkyl group, an alkoxy group, and an alkenyl group.
[0051] According to a thirteenth embodiment of the present disclosure, there is provided a method of manufacturing a separator for a lithium secondary battery as defined in any one of the eighth to twelfth embodiments,
[0052] The thermosetting phenolic resin is thermally cured at 120-200°C.
[0053] According to a fourteenth embodiment of the present disclosure, there is provided a method of manufacturing a separator for a lithium secondary battery as defined in any one of the eighth to thirteenth embodiments,
[0054] Wherein, based on 100 wt % of the inorganic particles, the content of the thermosetting phenolic resin is 0.1-20 wt %.
[0055] In yet another aspect of the present disclosure, a lithium secondary battery is provided, the lithium secondary battery comprising a cathode, an anode, and a separator interposed between the cathode and the anode, wherein the separator is the same as defined in any one of the above embodiments.
[0056] Beneficial Effects
[0057] The separator for lithium secondary battery according to one embodiment of the present disclosure includes a porous coating containing multiple inorganic particles and a binder polymer, wherein the binder polymer includes a thermosetting phenolic resin having at least one hydroxyl group and an aromatic ring. The thermosetting phenolic resin with this structure is used as a dispersant in a slurry for forming a porous coating, and is used as a binder polymer for fixing the inorganic particles. Therefore, the inorganic particles are well mixed with the binder polymer in the slurry, so that even without using a dispersant or using a reduced amount of dispersant, the adhesion between the electrode and the porous coating can also be kept good. In addition, the content of the dispersant can also be reduced, the content of the binder polymer can be increased, thereby improving the adhesion to the electrode.
[0058] Meanwhile, when an electrochemical device including the separator is exposed to high temperature due to fire, etc., the thermosetting phenolic resin is thermally cured to form a network structure. Therefore, a separator having enhanced heat resistance and improved thermal safety can be provided. DETAILED DESCRIPTION
[0059] Hereinafter, the preferred embodiments of the present disclosure will be described in detail with reference to the accompanying drawings. Before the description, it should be understood that the terms used in the specification and the accompanying claims should not be interpreted as being limited to the common meaning and dictionary meaning, but should be interpreted based on the meaning and concept of the technical aspects of the corresponding present disclosure on the basis of the principle that the inventor is allowed to appropriately define the terms for the best interpretation. Therefore, what is described herein is only a preferred embodiment for illustrative purposes and is not intended to limit the scope of the present disclosure, so it should be understood that other equivalents and modifications may be made thereto without departing from the scope of the present disclosure.
[0060] Throughout the specification, unless otherwise stated, the expression "a component includes or comprises an element" does not exclude the existence of any additional elements but means that the component may further include other elements.
[0061] Typically, lithium secondary batteries use porous polymer substrates as separators. Such porous polymer substrates may include a non-woven fabric substrate comprising polymer fibers and a film substrate made of a film obtained by polymer melt extrusion. Such polymer substrates, particularly film substrates, show undesirable thermal shrinkage behavior. Therefore, in order to improve the heat resistance of the separator, a porous coating comprising a plurality of inorganic particles and a binder polymer is introduced into at least one surface of the porous polymer substrate. When the porous coating is formed as described above, the heat resistance of the separator can be improved compared to using a porous polymer substrate alone.
[0062] Thermoplastic fluorinated binder polymers are mainly used as binder polymers. When the separator is exposed to a high temperature environment higher than the melting point of the binder polymer, the improvement of thermal safety is limited. In addition, in order to fully realize the performance of the lithium secondary battery, high adhesion between the porous coating and the electrode is required.
[0063] The present inventors have conducted intensive studies to solve the above problems. Therefore, the present disclosure is intended to provide a separator including a porous coating layer, which shows improved heat resistance when an electrochemical device including the separator is exposed to high temperature due to ignition, etc., and which has high adhesion to an electrode.
[0064] According to a first embodiment, there is provided a separator for a lithium secondary battery, comprising:
[0065] a porous polymer substrate having a plurality of pores; and
[0066] A porous coating layer is formed on at least one surface of the porous polymer substrate and includes a plurality of inorganic particles and a binder polymer, wherein the binder polymer includes a thermosetting phenolic resin having at least one hydroxyl group and an aromatic ring.
[0067] In a separator according to one embodiment of the present disclosure, when the separator is exposed to high temperature in an abnormal environment, the thermosetting phenolic resin is thermally cured to form a mesh structure. Here, the mesh structure refers to a structure formed by thermal curing of the thermosetting phenolic resin, wherein the mesh structure may be a three-dimensional mesh structure.
[0068] As described above, when the thermosetting phenolic resin in the porous coating undergoes a thermal curing reaction and forms a mesh structure at a high temperature in an abnormal environment, heat resistance and dimensional stability can be improved compared to a separator using a thermoplastic polymer. In other words, when a mesh structure is formed by the thermal curing reaction, the inorganic particles can be firmly held in the mesh structure until a very high temperature.
[0069] [Thermosetting phenolic resin]
[0070] The thermosetting phenolic resin has at least one hydroxyl group and an aromatic ring.
[0071] The thermosetting phenolic resin is heat-cured at a high temperature to form a network structure. Specifically, the thermosetting phenolic resin can be heat-cured at a high temperature of 120°C or higher, specifically at a high temperature of 120-200°C.
[0072] At the same time, the thermosetting phenolic resin having at least one hydroxyl group and an aromatic ring can act as a dispersant in the slurry for forming a porous coating. In this way, inorganic particles can be more easily dispersed in the slurry for forming a porous coating, so other dispersants can be omitted or their use can be reduced.
[0073] The thermosetting phenolic resin may include at least one of a novolac type phenolic resin represented by the following Chemical Formula 1 and a resole type phenolic resin represented by the following Chemical Formula 2, and may further include a modified phenolic resin. Specifically, any thermosetting phenolic resin obtained by aldehyde condensation of phenol and its derivatives may be used.
[0074] Here, Chemical Formula 1 is the same as that represented below.
[0075] [Chemical formula 1]
[0076]
[0077] In the above Chemical Formula 1, n is an integer of 1 or more, and R represents H and any one of an optionally substituted C1-C100 alkyl, alkoxy and alkenyl group. Here, the number of carbon atoms may be 1-100 or less, 1-50 or less, 1-30 or less, or 1-10 or less.
[0078] As used herein, "novolak-type phenolic resin" can be obtained by reacting a phenol compound with an aldehyde compound in the presence of an acidic catalyst. Since the novolac-type phenolic resin has a phenolic hydroxyl group, it is soluble in an alkali. However, when the novolac-type phenolic resin has an excessively high molecular weight, its solubility decreases.
[0079] Since the novolac type resin has fewer methylol groups for curing reaction, when a curing agent such as hexamethylenetetramine ((CH2)6N4) is added thereto and heated, a cured product having a three-dimensional structure can be formed.
[0080] The novolac phenolic resin may exist as an ortho-bond or a para-bond. According to one embodiment of the present disclosure, the ortho-bond / para-bond ratio of the novolac phenolic resin may be less than 0.2, specifically less than 0.1.
[0081] According to one embodiment of the present disclosure, the novolac phenolic resin may have at least two novolac phenolic resins having different ortho-bond / para-bond ratios. Here, when a high-para novolac phenolic resin having a greater amount of para-bonds relative to ortho-bonds is used, curing occurs more quickly at high temperatures, thereby providing a separator having higher safety.
[0082] The novolac phenolic resin preferably has a weight average molecular weight (Mw) of 1,000-4,000 and a polydispersity (Mw / Mn, wherein Mn is a number average molecular weight) of 2.0 or less. The novolac phenolic resin with a weight average molecular weight within the above-defined range is advantageous in ensuring heat resistance and fluidity during slurry preparation and formation of a thin film type porous coating. On the other hand, a novolac phenolic resin with a polydispersity of 2.0 or less is more advantageous in improving the dispersibility of inorganic particles. The novolac phenolic resin may have a hydroxyl equivalent of 100-200 g / eq.
[0083] Chemical Formula 2 is the same as that expressed below.
[0084] [Chemical formula 2]
[0085]
[0086] In the above Chemical Formula 2, n and m are each an integer of 1 or more, and R represents H and any one of an optionally substituted C1-C100 alkyl group, an alkoxy group, and an alkenyl group.
[0087] As used herein, the "resole-type phenolic resin" may be obtained by reacting a phenol compound with an aldehyde compound in the presence of a metal catalyst. The resol-type phenolic resin has a hydroxyl group and reacts with the novolac-type phenolic resin to form a crosslinked structure.
[0088] Here, the metal catalyst may include manganese, magnesium, zinc or the like. Specifically, the metal catalyst may be a metal acetate. For example, the metal catalyst may include manganese acetate, magnesium acetate and zinc acetate. Such metal catalysts may be used alone or in combination.
[0089] The resol type phenolic resin preferably has a weight average molecular weight of 420-1,500 and has a polydispersity (Mw / Mn, wherein Mn is a number average molecular weight) of 2.0 or less. The resol type phenolic resin with a weight average molecular weight within the above-defined range is advantageous in ensuring heat resistance and fluidity during slurry preparation and during formation of a thin film type porous coating. On the other hand, a resol type phenolic resin with a polydispersity of 2.0 or less is more advantageous in improving the dispersibility of inorganic particles. The resol type phenolic resin may have a hydroxyl equivalent of 100-200 g / eq.
[0090] Here, the weight average molecular weight can be measured by using gel permeation chromatography (GPC: gel permeation chromatography, PLGPC220, Agilent Technologies).
[0091] Specifically, the weight average molecular weight can be determined under the following analysis conditions:
[0092] - Column: PL MiniMixed B x 2
[0093] -Solvent: THF or DMF
[0094] -Flow rate: 0.3mL / min
[0095] -Sample concentration: 2.0mg / mL
[0096] -Injection volume: 10μL
[0097] - Column temperature: 40°C
[0098] -Detector: Agilent RI detector
[0099] - Standard: Polystyrene (calibrated with cubic function)
[0100] -Data processing: ChemStation
[0101] According to one embodiment of the present disclosure, the thermosetting phenolic resin may include 2,3,4-trihydroxybenzophenone, 2,4,6-trihydroxybenzophenone, 2,2′-tetrahydroxybenzophenone, 4,4′-tetrahydroxybenzophenone, 2,3,4,3′-tetrahydroxybenzophenone, 2,3,4,4′-tetrahydroxybenzophenone, 2,3,4,2′-tetrahydroxy 4′-methylbenzophenone, 2,3,4,4′-tetrahydroxy 3′-methoxybenzophenone, 2,3,4,2′-pentahydroxybenzophenone, 2,3,4,6′-pentahydroxybenzophenone, 2,4,6,3′-hexahydroxybenzophenone, 2,4,6,4′-hexahydroxybenzophenone, 2,4,6,5′-hexahydroxybenzophenone , 3,4,5,3′-hexahydroxybenzophenone, 3,4,5,4′-hexahydroxybenzophenone, 3,4,5,5′-hexahydroxybenzophenone, bis(2,4-dihydroxyphenyl)methane, bis(p-hydroxyphenyl)methane, tris(p-hydroxyphenyl)methane, 1,1,1-tris(p-hydroxyphenyl)ethane, bis(2,3,4-trihydroxyphenyl)methane, 2,2-bis(2,3,4-trihydroxyphenyl))propane, 1,1,3-tris(2,5-dimethyl 4-hydroxyphenyl)-3-phenylpropane, 4,4′-[1-[4-[1-[4-hydroxyphenyl]-1-methylethyl]phenyl]ethylene]bisphenol, bis(2,5-dimethyl 4-hydroxyphenyl)-2-hydroxyphenylmethane or the like. These compounds may be used alone, or two or more thereof may be used in combination to prepare the resin. For example, the thermosetting phenolic resin may be a phenol-formaldehyde resin.
[0102] According to one embodiment of the present disclosure, when the thermosetting phenolic resin is thermally cured under an abnormally high temperature environment, it may form a network structure having a structure shown below.
[0103] For example, the network structure can be represented by the following chemical formula 3:
[0104]
[0105] According to one embodiment of the present disclosure, after the thermosetting phenolic resin is thermally cured to form a network structure, the inorganic particles in the porous coating layer may be disposed in the network structure.
[0106] Here, based on 100 wt % of the content of the inorganic particles, the content of the thermosetting phenolic resin may be specifically 0.1-20 wt %, and more specifically 0.5-15 wt %. Within the above-defined range, heat resistance can be improved without significantly increasing the interface resistance between the porous polymer substrate and the porous coating layer.
[0107] [Inorganic particles]
[0108] According to one embodiment of the present disclosure, there is no particular limitation on inorganic particles, as long as they are electrochemically stable. In other words, the inorganic particles that can be used herein are not particularly limited, as long as they do not cause oxidation and / or reduction reactions within the operating voltage range of the applicable electrochemical device (e.g., 0-5V based on Li / Li+). In particular, when inorganic particles with a high dielectric constant are used as inorganic particles, the ionic conductivity of the electrolyte can be increased by increasing the dissociation degree of electrolyte salts such as lithium salts in liquid electrolytes.
[0109] For the above reasons, the inorganic particles may be inorganic particles having a dielectric constant of 5 or more, inorganic particles having a lithium ion transporting capability, or a combination thereof.
[0110] The inorganic particles having a dielectric constant of 5 or more may include particles selected from the group consisting of Al2O3, SiO2, ZrO2, AlOOH, TiO2, BaTiO3, Pb(Zr, Ti)O3 (PZT, wherein 0<x<1), Pb 1-x La x Zr 1-y Ti y O3(PLZT, where 0<x<1, 0<y<1), (1-x)Pb(Mg 1 / 2 Nb 2 / 3 ) 3-x Any one of the group consisting of PbTiO3 (PMN-PT, where 0<x<1), hafnium oxide (HfO2), SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZO3 and SiC, or a mixture of two or more thereof.
[0111] The inorganic particles having lithium ion transport capability may be selected from lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y (PO4)3, 0<x<2, 0<y<3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, 0<x<2, 0<y<1, 0<z<3), (LiAlTiP) x Oy Base glass (1<x<4, 0<y<13), lanthanum lithium titanate (Li x La y TiO3, 0<x<2, 0<y<3), lithium germanium thiophosphate (Li x Ge y P z S w , 0<x<4, 0<y<1, 0<z<1, 0<w<5), lithium nitride (Li x N y , 0<x<4, 0<y<2), SiS2-based glass (Li x Si y S z , 0<x<3, 0<y<2, 0<z<4) and P2S5 based glass (Li x P y S z , 0<x<3, 0<y<3, 0<z<7), or a mixture of two or more thereof.
[0112] In addition, the average particle size of the inorganic particles is not particularly limited. However, the inorganic particles preferably have an average particle size of 0.001-10 μm to form a coating with uniform thickness and provide a suitable porosity. Specifically, the inorganic particles may have an average particle size of 100 nm or more, 150 nm or more, or 200 nm or more, and 1000 nm or less, 900 nm or less, 800 nm or less, or 700 nm or less.
[0113] [Non-phenolic resin]
[0114] According to one embodiment of the present disclosure, the porous coating layer may further include a non-phenolic resin as a binder polymer in addition to the above-mentioned thermosetting phenolic resin.
[0115] The non-phenolic resin may be one currently used in the art to form a porous coating. In particular, a non-phenolic resin having a glass transition temperature (T g ) is a polymer having a temperature of -200°C to 200°C. This is because such a polymer can improve the mechanical properties of the porous coating layer finally formed, such as flexibility and elasticity. This non-phenolic resin acts as a binder that connects and stably fixes the inorganic particles to each other, thereby helping to prevent the deterioration of the mechanical properties of the separator having the porous coating layer.
[0116] In addition, the non-phenolic resin is not required to have ion conductivity. However, when a polymer with ion conductivity is used, the performance of the electrochemical device can be further improved. Therefore, a non-phenolic resin with a dielectric constant as high as possible can be used. In fact, since the degree of dissociation of salts in the electrolyte depends on the dielectric constant of the solvent used for the electrolyte, a non-phenolic resin with a higher dielectric constant can increase the degree of dissociation of salts in the electrolyte. The non-phenolic resin may have a dielectric constant in the range of 1.0-100 (measured at a frequency of 1kHz), specifically 10 or more.
[0117] In addition to the above functions, the non-phenolic resin may be characterized in that the binder polymer is gelled when impregnated with a liquid electrolyte and thus exhibits a high degree of swelling. Therefore, the solubility parameter (i.e., Hildebrand solubility parameter) of the non-phenolic resin is 15-45 MPa. 1 / 2 or 15-25MPa 1 / 2 and 30-45MPa 1 / 2 Therefore, compared with hydrophobic polymer resins such as polyolefins, hydrophilic polymer resins having many polar groups can be used more. When the solubility parameter is less than 15MPa 1 / 2 and greater than 45MPa 1 / 2 When the non-phenolic resin is used, it is difficult to swell with conventional liquid electrolytes for batteries.
[0118] Non-limiting examples of the non-phenolic resin include polyvinylidene fluoride, polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polyvinylidene fluoride-co-trifluoroethylene, polyvinylidene fluoride-co-chlorotrifluoroethylene, polymethylmethacrylate, polyethylhexyl acrylate, polybutylacrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinylacetate, polyethylene-co-vinyl acetate, polyethylene oxide, oxide), polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinylalchol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, etc.
[0119] The separator according to one embodiment of the present disclosure may further include other additives such as a dispersant as a component of the porous coating layer in addition to the inorganic particles and the binder polymer.
[0120] Although the thickness of the porous coating layer is not particularly limited, it may be 0.5-20 μm, specifically 1.5-10 μm based on single-side coating. In addition, the porosity of the porous coating layer is not particularly limited, but the porous coating layer preferably has a porosity of 35%-85%.
[0121] [Porous polymer substrate]
[0122] In the separator according to one embodiment of the present disclosure, the porous polymer substrate may be a porous polymer film substrate or a porous polymer nonwoven fabric substrate.
[0123] The porous polymer membrane substrate may be a porous polymer membrane including polyolefins such as polyethylene or polypropylene. For example, such a polyolefin porous polymer membrane substrate may achieve a shutdown function at a temperature of 80-150°C.
[0124] Here, the polyolefin porous polymer film may be formed of a polymer including a polyolefin polymer, such as polyethylene including high density polyethylene, linear low density polyethylene, low density polyethylene or ultra high molecular weight polyethylene, polypropylene, polybutene or polypentene, alone or in combination of two or more thereof.
[0125] In addition, the porous polymer film substrate can be obtained by molding various polymers (such as polyester) other than polyolefin into a film shape. In addition, the porous polymer film substrate can have a stacked structure of two or more film layers, wherein each film layer can be formed by a polymer including the above polymer, such as polyolefin or polyester, alone or in combination of two or more of them.
[0126] In addition, the porous polymer film substrate and the porous polymer non-woven fabric substrate may be formed of polymers other than the above-mentioned polyolefins, alone or in combination, and the polymers include polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenyleneoxide, polyphenylenesulfide or polyethylenenaphthalene.
[0127] In addition, although there is no particular limitation on the thickness of the porous polymer substrate, the thickness of the porous polymer substrate is 1-20 μm, specifically 5-15 μm. Although there is no particular limitation on the size and porosity of the pores present in the porous polymer substrate, the pore size and porosity may be 0.01-50 μm and 20%-75%, respectively.
[0128] Hereinafter, a method of manufacturing a separator according to one embodiment of the present disclosure will be described in detail. However, the scope of the present disclosure is not limited to the following embodiments.
[0129] Specifically, inorganic particles are dispersed in a first solvent, and a thermosetting phenolic resin having at least one hydroxyl group and an aromatic ring is dissolved therein to prepare an inorganic particle dispersion (S1).
[0130] Here, the method may further include the step of mixing a polymer solution including a non-phenolic resin dissolved in a second solvent with the inorganic particle dispersion of step (S1). In addition, the inorganic particle dispersion may further include a dispersant.
[0131] Here, the first solvent and the second solvent may be the same or different.
[0132] Here, preferably the first solvent and the second solvent each have a solubility parameter similar to the solubility parameter of the binder polymer, i.e. the thermosetting phenolic resin and the non-phenolic resin, and have a low boiling point (boiling point). This is because such a solvent is conducive to uniform mixing and subsequent solvent removal. The limiting examples of operable solvent include any one selected from water, C2-C5 alcohol, acetone, tetrahydrofuran, methylene dichloride, chloroform, dimethyl formamide, N-methyl-2-pyrrolidone, methyl ethyl ketone and cyclohexane, or two or more mixtures thereof.
[0133] Then, a slurry for forming a porous coating layer including the inorganic particle dispersion is coated on at least one surface of a porous polymer substrate, followed by drying to form a porous coating layer ( S2 ).
[0134] Although the process of coating the slurry for forming the porous coating on the porous polymer substrate is not particularly limited, it is preferred to use a slit coating process or a dip coating process. The slit coating process includes coating the composition supplied through a slit die on the entire surface of the substrate, and the thickness of the coating can be controlled according to the flow rate supplied from the metering pump. In addition, the dip coating process includes coating by immersing the substrate in a tank containing the composition, and the thickness of the coating can be controlled according to the concentration of the composition and the speed of removing the substrate from the composition tank. In addition, in order to more accurately control the coating thickness, post-metering can be performed by Mayer rods, etc. after dipping.
[0135] Then, the porous polymer substrate coated with the slurry for forming the porous coating layer is dried by using a dryer such as an oven, thereby forming a porous coating layer on at least one surface of the porous polymer substrate.
[0136] In the porous coating, the inorganic particles may be dispersed in a matrix of the binder polymer. The binder polymer may be a thermosetting phenolic resin or a non-phenolic resin, or both.
[0137] In addition, the inorganic particles are combined with each other by the binder polymer, and they are stacked and contact each other at the same time. Therefore, a gap volume (interstitial volume) is formed between the inorganic particles, and the gap volume (Interstitial Volume) between the inorganic particles becomes an empty space to form a hole. In other words, the inorganic particles are attached to each other by the binder polymer so that their binding state can be maintained. For example, the binder polymer connects and fixes inorganic particles to each other. In addition, the hole of the porous coating is a hole formed by the gap volume (interstitial volume) between the inorganic particles that become the empty space. The space is limited by the inorganic particles that are substantially facing each other in the structure of the close packing or dense packing (closely packed or densely packed) of the inorganic particles.
[0138] The inorganic particles, the thermosetting phenolic resin, the non-phenolic resin, and the porous polymer substrate are the same as described above, and a detailed description thereof will be omitted.
[0139] In another aspect of the present disclosure, a lithium secondary battery is provided, the lithium secondary battery including a cathode, an anode, and a separator interposed between the cathode and the anode, wherein the separator is the above separator according to one embodiment of the present disclosure.
[0140] Specifically, the lithium secondary battery may include a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery, or a lithium ion polymer secondary battery.
[0141] The two electrodes used in combination with the separator according to the present disclosure, i.e., the cathode and the anode, are not particularly limited and can be obtained by combining the electrode active material with the electrode current collector using conventional methods known in the art. In the electrode active material, non-limiting examples of cathode active materials include conventional cathode active materials that can be used in the cathode of conventional electrochemical devices. Specifically, lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, lithium iron oxide, or lithium composite oxides comprising a combination thereof are preferably used. Non-limiting examples of anode active materials include conventional anode active materials that can be used in the anode of conventional electrochemical devices. Specifically, lithium intercalation materials such as lithium metal or lithium alloys, carbon, petroleum coke, activated carbon, graphite, or other carbonaceous materials are preferably used. Non-limiting examples of cathode current collectors include foils made of aluminum, nickel, or a combination thereof. Non-limiting examples of anode current collectors include foils made of copper, gold, nickel, copper alloys, or a combination thereof.
[0142] The electrolyte that can be used in the electrochemical device according to the present disclosure is A + B - A salt of the structure + Including such as Li + 、Na + , K + or combinations thereof, and B- includes alkali metal cations such as PF6 - 、BF4 - , Cl - Br - ,I - 、ClO4 - 、AsF6 - 、CH3CO2 - CF3SO3 - 、N(CF3SO2)2 - 、C(CF2SO2)3 - Or a combination thereof, the salt is dissolved or dissociated in an organic solvent including propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), γ-butyrolactone (γ-butyrolactone) or a combination thereof. However, the present disclosure is not limited thereto.
[0143] According to the manufacturing process of the final product and the properties required of the final product, the injection of the electrolyte can be carried out in an appropriate step during the process of manufacturing the battery. In other words, the injection of the electrolyte can be carried out before the assembly of the battery or in the final step of the battery assembly.
[0144] Each embodiment will be described more fully below, so that the present disclosure can be easily understood. However, the following embodiments can be embodied in a variety of different forms, and should not be interpreted as being limited to the exemplary embodiments set forth therein. On the contrary, these exemplary embodiments are provided to make the present disclosure thorough and complete, and to fully convey the scope of the present disclosure to those skilled in the art.
[0145] Example 1
[0146] First, aluminum hydroxide (Al(OH)3) particles (particle size: 800 nm) as inorganic particles are introduced into acetone as the first solvent to a solid content of 30%. Here, "solid content" refers to the content of the powder obtained after drying the solvent, expressed as a percentage based on the total content of the solvent and the composition of the components. Next, isopropyl trioleyl titanate (Isopropyl trioleyl titanate) and a thermosetting phenolic resin (Kangnam Chemical, resol type phenolic resin, thermosetting temperature: about 150°C, soluble in acetone, solid content 50%, viscosity: 250 mPas at 25°C) as dispersants are introduced into the composition shown in Table 1 below and stirred for 2 hours. In this way, an inorganic particle dispersion is prepared, which includes the inorganic particles dispersed in the first solvent and the thermosetting phenolic resin dissolved therein.
[0147] Then, as shown in Table 1, polyvinylidene fluoride-co-hexafluoropropylene (PVDF-HFP) as a non-phenolic resin was introduced into acetone as a second solvent and dissolved at 50° C. for about 4 hours to prepare a polymer solution.
[0148] The inorganic particle dispersion prepared as above was mixed with the polymer solution so that the weight ratio of the inorganic particles to the binder polymer was 75:25, and then the inorganic particles were crushed and dispersed using a ball milling process for 3 hours to obtain a slurry with a solid content of 18% for forming a porous coating.
[0149] Then, at 23°C and 45% relative humidity, the slurry for forming a porous coating layer was coated on both sides of a 9 μm thick polyethylene porous membrane (porosity: 43%, air permeability time: 110 sec / 100 mL, resistance: 0.45 ohm) by a coating process, so that the total loading amount of the slurry was 9.5 g / m 2 , and then dried to obtain a separator with a porous coating.
[0150] Embodiment 2-7
[0151] The separator was obtained in the same manner as in Example 1, except that the kinds and contents of the components contained in the slurry were controlled as shown in Table 1.
[0152] Comparative Examples 1-4
[0153] The separator was obtained in the same manner as in Example 1, except that the kinds and contents of the components contained in the slurry were controlled as shown in Table 1.
[0154] [Table 1]
[0155]
[0156] [Test method]
[0157] 1) Thickness measurement method
[0158] The thickness of the separator was measured by using a thickness gauge (Mitutoyo, VL-50S-B).
[0159] 2) Measurement method of thermosetting temperature of thermosetting phenolic resin
[0160] The exothermic peak temperature of the thermosetting phenolic resin measured using a differential scanning calorimeter (DSC) was determined as the thermosetting temperature of the resin.
[0161] 3) Air permeability measurement method
[0162] The air permeability of the separator was measured using a Gurley type air permeability analyzer according to JIS P-8117. Here, the air permeability of 100 mL of air was measured through a 28.6 mm diameter and 645 mm area. 2 The time required.
[0163] 4) Method for measuring the adhesion between the electrode and the separator (Lami Strength)
[0164] Each separator according to the embodiment and the comparative example is cut into a size of 25mm×100mm. The prepared separator is stacked with the anode, and the resulting stack is inserted between PET films having a thickness of 100μm, and then adhered using a flat press. Here, the flat press is heated and pressed at 70°C and a pressure of 600kgf for 1 second. The adhered separator and anode (artificial graphite, carbon black, carboxymethyl cellulose (CMC, Carboxy Methyl Cellulose) and styrene-butadiene rubber (SBR, Styrene-Butadiene Rubber) with a weight ratio of 96:1:2:2) are attached to a glass slide by using double-sided tape. The end of the adhesive surface of the separator is peeled off (10mm or less from the end of the adhesive surface), and it is attached to a 25mm×100mm PET film using a single-sided tape so that they are connected to each other in the longitudinal direction. Then, the glass slide was mounted on the lower support of a UTM instrument (LLOYD Instrument LF Plus), and the PET film attached to the separator was mounted on the upper support of the UTM instrument, and the force required to separate the anode from the porous coating facing the anode was measured by applying force at an angle of 180° and a rate of 300 mm / min.
[0165] 5) Determination of thermal shrinkage
[0166] The heat shrinkage rate was calculated according to the formula: (initial length - length after heat shrinkage at 150° C. for 30 minutes) / (initial length)×100.
Claims
1. A lithium secondary battery comprising a cathode, an anode and a separator interposed between the cathode and the anode, The separator comprises: a porous polymer substrate having a plurality of pores; and a porous coating layer formed on at least one surface of the porous polymer substrate and comprising a plurality of inorganic particles and a binder polymer, wherein the binder polymer comprises a thermosetting phenolic resin having at least one hydroxyl group and an aromatic ring, The thermosetting phenolic resin comprises a resol-type phenolic resin represented by the following chemical formula 2: [Chemical formula 2] In Chemical Formula 2, n and m are each an integer of 1 or more, and R represents H and any one of an optionally substituted C1-C100 alkyl group, an alkoxy group, and an alkenyl group, wherein the resol type phenolic resin has a hydroxyl equivalent of 100-200 g / eq, Wherein, based on 100 wt % of the inorganic particles, the content of the thermosetting phenolic resin is 0.5-15 wt %.
2. The lithium secondary battery according to claim 1, wherein the thermosetting phenolic resin is thermally cured at 120-200°C. 3 . The lithium secondary battery according to claim 1 , wherein the thermosetting phenolic resin is a phenol formaldehyde resin. 4 . The lithium secondary battery according to claim 1 , wherein the binder polymer further comprises a non-phenolic resin in an amount of 0.1 to 50 wt % based on 100 wt % of the content of the inorganic particles. 5 . The lithium secondary battery according to claim 1 , wherein the porous polymer substrate has a thickness of 1 to 20 μm, and the porous coating layer has a thickness of 0.5 to 20 μm based on a single-side coating.
6. A method for manufacturing a lithium secondary battery, the lithium secondary battery comprising a cathode, an anode and a separator interposed between the cathode and the anode, the method comprising the following steps: (S1) by dispersing inorganic particles in a first solvent and dissolving a thermosetting phenolic resin having at least one hydroxyl group and an aromatic ring therein, To prepare an inorganic particle dispersion; and (S2) applying a slurry for forming a porous coating layer including the inorganic particle dispersion on at least one surface of a porous polymer substrate, followed by drying to form a porous coating layer, The thermosetting phenolic resin comprises a resol-type phenolic resin represented by the following chemical formula 2: [Chemical formula 2] In Chemical Formula 2, n and m are each an integer of 1 or more, and R represents H and any one of an optionally substituted C1-C100 alkyl group, an alkoxy group, and an alkenyl group, wherein the resol type phenolic resin has a hydroxyl equivalent of 100-200 g / eq, Wherein, based on 100 wt % of the inorganic particles, the content of the thermosetting phenolic resin is 0.5-15 wt %.
7. The method for manufacturing a lithium secondary battery according to claim 6, further comprising the following steps: The inorganic particle dispersion of step (S1) is mixed with a polymer solution including a non-phenolic resin dissolved in a second solvent.
8. The method for manufacturing a lithium secondary battery according to claim 7, wherein the first solvent and the second solvent each independently include any one compound selected from water, C2-C5 alcohol, acetone, tetrahydrofuran, dichloromethane, chloroform, dimethylformamide, N-methyl-2-pyrrolidone, methyl ethyl ketone and cyclohexane, or a mixture of two or more thereof. 9 . The method for manufacturing a lithium secondary battery according to claim 6 , wherein the inorganic particle dispersion further comprises a dispersant.
10. The method for manufacturing a lithium secondary battery according to claim 6, wherein the thermosetting phenolic resin is thermally cured at 120-200°C.